Analyses of herd offtake and marketing of live and dressed trypanotolerant cattle: A case study from the Gambia - Agyemang, K.; Clifford, D.J.; Barrow, A.; Corr, N.; Dwinger, R.H. (1998)
Data on approximately 4,000 head of N'Dama cattle kept in 60 herds under traditional management systems in The Gambia were analysed to estimate annual herd offtake rates during a 5 year period (1986-1990). Farm-gate sale prices and weight at sale of 428 cattle were analysed by least-squares ANOVA to determine factors influencing prices. Similarly, pre-slaughter and carcass characteristics data on 1,724 N'Dama cattle collected from the national abattoir, Abuko, in 1989/90 were analysed. Results from the analyses showed very low animal off take rates (<7 percent). Prices during the years following the devaluation of the local currency were higher than those charged during the pre-devaluation year. The asset value of cattle, even for those considered unproductive, increased higher relative to cash savings that would have accrued had the animals been sold prior to the devaluation. Analysis of the carcass data showed high reproductive wastage through slaughtering of pregnant cows in response to dry season feed shortages. This action was considered economically sound as the alternative was death of the stock. It was concluded that the reluctance of traditional stock owners to sell animals may in part stem from economic consideration and that when faced with production constraints such as shortfalls in feed supplies, farmers do sell animals readily. However, stock sold in emaciated conditions as observed in this study are not likely to meet the requirements of importers or attract good prices at the local markets.